Reduction of Silent Information Regulator 1 Activates Interleukin-33/ST2 Signaling and Contributes to Neuropathic Pain Induced by Spared Nerve Injury in Rats - Zeng, Yanyan; Shi, Yu; Zhan, Hongrui; Liu, Wei; Cai, Guiyuan; Zhong, Haili; Wang, Yaping; Chen, Shangjie; Huang, Shimin; Wu, Wen (Frontiers in Molecular Neuroscience, 2020)
Emerging studies have demonstrated that interleukin (IL)-33 and its receptor ST2 act as key factors in inflammatory diseases. Moreover, accumulating evidence has suggested that cytokines, including tumor necrosis factor (TNF)-α and IL-1β, trigger an inflammatory cascade. SIRT1 has been shown to suppress the expression of inflammatory cytokines. However, the effects of SIRT1 on IL-33/ST2 signaling and initiation of the inflammatory cascade via modulation of TNF-α and IL-1β by IL-33 remain unclear. In the present study, we found that the dorsal root ganglion (DRG) IL-33 and ST2 were upregulated in a rat model of spared nerve injury (SNI) and intrathecal injection of either IL-33 or ST2 antibodies alleviated mechanical allodynia and downregulated TNF-α and IL-1β induced by SNI. In addition, activation of SIRT1 decreased enhanced DRG IL-33/ST2 signaling in SNI rats. Artificial inactivation of SIRT1 via intrathecal injection of an SIRT1 antagonist could induce mechanical allodynia and upregulate IL-33 and ST2. These results demonstrated that reduction in SIRT1 could induce upregulation of DRG IL-33 and ST2 and contribute to mechanical allodynia induced by SNI in rats.